Psychopathologies in deleuze and guattari and merleau-ponty: from the power of institutions to the power of being - Eleutério da Silva Junior , Francelino; Taveira da Cruz, Ronald (Seven Editora, 2023)
This paper contemplates the conclusion of research developed in the period of one year, 2021-2022, from the Voluntary Scientific Initiation of the Federal University of Delta do Parnaíba – UFDPAR. Its critical assumptions, as well as its results, stem from the meetings and discussion seminars of the study group – NEM (Centre of Mental Studies) – thus characterizing itself as a critical and investigative study of literature review. The current and consolidated literature is an important tool for understanding the ways of understanding psychopathological phenomena and the symptomatic ways that lead to the identification of the pathology in favor of normality without recognizing the processes that promote illness, considering its phenomena and symptoms. The objective of this article is to create an important precedent for the critical incitement of the practices of modern psychology and other scientific devices in the light of the philosophy of what psychopathologies are in their embryonic sense, between the construction of normality of the body and psychopathologies in the course of your healing process. The study focused on the foundations of Merleau-Ponty's phenomenology and the philosophy of difference with Deleuze and Guattari and other authors, thus weaving a theoretical and critical framework for building an understanding of the symptoms and the relational phenomenon in the face of what is normal and pathological.DOI: https://doi.org/10.56238/devopinterscie-148